PENERAPAN PROGRAM SUPER DEAL UNTUK MENURUNKAN BERAT BADAN BERLEBIH PADA KELUARGA MENGGUNAKAN APLIKASI SMARTPHONE - Desy Rizki Ariani; Kusiyuwati Kusiyuwati; Sri Ayu Fatmayanti (Jurnal Abdimas Indonesia, 2025)
Overweight or obesity is excess fat in the body. If the large amount of energy (in the form of food) that enters the body exceeds the amount expended, body weight will increase and most of the excess energy will be stored as fat. Family as a form of support system with the SUPER DEAL program (Support Family Ideal Body Weight). So that the focus is not only one individual who is sick or has problems but also the support of all family members. To improve the ability to control weight, there needs to be technology-based innovation that makes it easier for families to access health information and weight management presented on smartphones. This program was implemented in 5 families who experienced overweight problems, in December - February 2025 in Karawang district. The SUPER DEAL program in Karawang district succeeded in increasing the knowledge, attitudes and skills of families in dealing with the problem of excess weight. The results of weight loss were reported on average from 77 kg to 72 kg, which means that the weight loss success was 6% after the SUPER DEAL program was carried out.